Macrophage activation syndrome successfully treated with eculizumab and emapalumab: a case report - Faggioli, Paola; Galeazzi, Marianna; Ferrari, Carlotta; Capelli, Francesca; Marchesi, Chiara; Marchionni, Lucia; Castelnovo, Laura; Tamburello, Antonio; Capparelli, Eugenio; Campidelli, Cristina; Mazzone, Antonino (Frontiers in Immunology, 2025)
Hemophagocytic lymphohistiocytosis (HLH) is a hyperinflammatory syndrome, often referred to as macrophage activation syndrome (MAS) in the context of autoimmune disease-induced forms. We report the case of a 41-year-old woman with a previous diagnosis of Crohn’s disease complicated by dermatomyositis, who was admitted in our hospital for the acute onset of fever, pancytopenia, and disseminated intravascular coagulation (DIC). The laboratory findings documented hyperferritinemia, hypertransaminasemia, increased lactate-dehydrogenase (LDH), hypertriglyceridemia, and elevation of inflammatory indices, along with complement consumption. MAS was confirmed by examination of the bone marrow. Consequently, the patient was treated with high doses of glucocorticoids, subcutaneous anakinra, and intravenous immunoglobulin (IVIg). Due to the persistence of signs of thrombotic microangiopathy, we started therapy with eculizumab which stabilized the patient without improvement, so we added emapalumab, resulting in clinical improvement and normalization of blood tests.